Study of Hemoglobin and Calcium Phosphorus Product in Patients with Chronic Kidney Disease (Med Phoenix, 2023)
Introduction: Kidneys play a vital role in the metabolism of minerals such as calcium and phosphorous. Moreover, kidney is involved in the production of erythropoietin hormone.The bone marrow suppression may occur in Chronic Kidney Disease (CKD) patients. Reduced hemoglobin and increased calcium phosphorous product concentration is also common in CKD patients.The current study is aimed to find out the impact of CKD in calcium phosphorous product and hemoglobin level in Nepalese population.Materials And Methods: One hundred consecutive diagnosed cases of CKDpatients were enrolled retrospectively for the study. Calcium, phosphorous, urea, creatinine and other biochemical parameters were measured in fully automated biochemistry analyzer and hemoglobin was measured using hematology analyzer (Beckman Coulter DxH500 Automated Hematology analyzer).Results: The current study revealed the hemoglobin and calcium phosphorous product in CKD patients.The Calcium Phosphorous Product (CaP) of 69 subjects were having less than